Mechanical and Thermal Properties of Bamboo-Cotton Textile Waste Reinforced Recycled Polypropylene Composite for Eco-Packaging Applications - Nur Azra Fathiah Azunny; Mazatusziha Ahmad; Reazul Haq Abdul Haq (Progress in Engineering Application and Technology, 2026)
The study investigates the mechanical and thermal properties of bamboo-cotton textile waste reinforced recycled polypropylene (rPP) composites, addressing growing concerns over waste production and the need for sustainable materials. Alkaline treatment of the textile waste was performed, followed by composite preparation through internal mixing and compression molding, with varying fiber loadings of 5%, 15%, 20%, and 25%. Characterization techniques included FTIR and FESEM, indicating enhanced fiber surface roughness after chemical treatment, which improved mechanical bonding with rPP. Mechanical tests revealed that as the fiber content rises from 5% to 20%, there is a notable improvement in tensile strength and Young’s modulus, while thermal analysis indicated that the 5% composite had superior thermal stability. Therefore, higher fiber loads improve load-bearing capabilities, and lower fiber loads allow for more ordered molecular arrangement within the rPP. Results suggest that BCTW-reinforced rPP composites present a viable, eco-friendly alternative for packaging materials.